THE USE OF FIX THE MISTAKE GAME BOOK TO IMPROVE STUDENTSâ€™ GRAMMAR MASTERY - Ari Satria (INOVISH JOURNAL, 2020)
The objective of the research was to describe the learning atmosphere during the implementation of â€œFix the Mistake Game Bookâ€. Besides, the research was also designed to know how the improvement of the studentsâ€™ grammar during the implementation of â€œFix the Mistake Game Bookâ€. This research was a classroom action research. The research was carried out in first year students of MTSM Penyasawan. This research was conducted in two cycles by following the procedure of action research, i.e. planning, implementing, observing, and reflecting. The results of the research showed that the learning atmosphere also improved. The class became more enthusiastic and feel comfort. Furthermore, Fix The Mistake Game Book was able to improve the studentsâ€™ grammar mastery. It was proven by the increase of the studentsâ€™ mean score from 41.34 in pre-test to 47.83 in cycle 1, and 49.84 in cycle 2, although the results of the research were just a little bit improvement. It could be concluded that the use of Fix the Mistake Game Book has proven to be an effective way in teaching-learning of grammar on first year of MTSM Penyasawan.